Abolishing biofuel policies: Possible impacts on agricultural price levels, price variability and global food security. (May 2016) - Araujo Enciso, Sergio René; Fellmann, Thomas; Pérez Dominguez, Ignacio; Santini, Fabien
Highlights: ​We simulate a 10-years forward looking scenario where biofuel policies are abolished. Effects on price variability of biofuels are significant. Effects on price variability of agricultural commodities are only marginal. Price levels decrease moderately for agricultural commodities in most regions. However, food use increases would remain low for most crops and regions. Abstract: In this paper we assess the impact of abolishing biofuel policies (mandates, tax credits, import and export tariffs) on agricultural price levels and price variability as well as some aspects related to global food security. For the analysis we employ a recursive-dynamic agricultural multi-commodity model within a stochastic framework. Results of the 10-years forward looking scenario indicate that the removal of biofuel policies would have a significant effect on price variability of biofuels, but only a marginal impact on the variability of agricultural commodity prices. Without biofuel policies, global biofuel demand would decrease by 25% for ethanol and 32% for biodiesel. Moreover, prices would only moderately decrease for ethanol feedstock commodities like wheat and coarse grains, while prices for biodiesel feedstock commodities, specifically vegetable oils, would be more affected. Due to competing uses of crop production such as feed and industrial use, abolishing biofuel policies would not necessarily lead to an increase in global food security, as food use increases would remain low for most crops and regions.